Study of latex glove associated dermatoses among nurses in a tertiary care hospital - Tomy, Chitra; Joseph, Bobby; Madhukara, J (Indian Dermatology Online Journal, 2021)
Introduction: Natural rubber latex (NRL) is processed from Hevea brasiliensis trees. Allergic reactions to certain proteins in the latex manifest as immediate hypersensitivity reactions and allergic reactions to chemicals added to latex during processing manifest as allergic contact dermatitis. Healthcare workers (HCWs) are at increased risk of developing latex allergies. As little data is available from India, this study was directed toward identifying the prevalence of latex glove-related dermatoses among nurses and the factors leading to it. Methodology: This cross-sectional study was undertaken among nurses in a private tertiary care hospital. Results: A total of 700 nurses were included in the study. Symptoms of latex allergy were present in 74 (10.6%) of study subjects, out of which 69 (9.9%) had features of contact dermatitis. Patch test was done in 50 subjects and was positive in 12 (24%); among them, patch test antigens were positive in 9 (18%) and a positive result to glove piece was seen in 3 subjects. Conclusions: Latex allergy in India is a significant problem; though lesser compared to western countries, its prevalence necessitates the development of pre-employment protocols to avoid workplace morbidity.